The Struggle against Extremism in the Supply Chain of International Human Rights Law - Suhail Hussein Al-Fatlawi (International Journal of Supply Chain Management, 2018)
The world in general and the Middle East, in particular, are witnessing a new wave of extremist movements that want to impose their backward ideas on peoples. These groups use armed force to kill innocent women, children and the elderly. Although human beings are considered one of the origin and they share common features, but they differ in colors and objects and shapes, depending on the different nature from which they come, and factors affecting the configuration profile for a person, because of mixing between human beings. As human beings different in ideas and aspirations, customs and beliefs and national assets, and differ in the homeland and psychological trends and configuration Profile, historical and cultural factors: This is what creates barriers for long relationship between them. Diversity and differences between the different communities, but it has become within the same community was not considered. It was this diversity and difference and still is, one of the reasons for the destruction and abuse, the victim went millions of people. In this paper the struggle against extremism in the supply chain of international human rights law will be investigated.